Project financing in the investment and construction complex - O. E. Astafieva; A. V. Kozlovsky; N. A. Moiseenko (Вестник университета)
The problems arising in organizations during the process of investment activities have been considered. The results of financing and implementation of projects and programs have been analysed and interpreted consistently. The issues of expediency of using the profitability indicators of the capital or assets of the company, which requires for the project implementation, have been touched upon. Approaches to the possibility of using the project financing mechanism, have been substantiated. Attention has been paid to the positive and negative aspects of the application of project financing for the company investment activities. It has been noted that project financing is usually used in the implementation of large investment projects, which combine the economic interests of the state and private investors. Particular attention has been paid to the issues of project and program management within the digital environment in order to provide a unified information base. The analysis of possible risks when using the project financing mechanism has been provided and the approaches to influencing the emerging risks have been defined. The result of the study was the formation of factors affecting the effectiveness of the project financing mechanism in the implementation of investment projects and programs.